Hávamál e Baldrs draumar : I detti dell'Eccelso e I sogni di Baldr : dai codici Reykjavík, Safn Árna Magnússonar,GKS 2365 4to e København, Den ArnamagnæanskeSamling, AM 748 I a 4to - A. Meregalli (Novus Press, 2018)
This is an Italian translation of "Hávamál" (stanzas 1-12) and "Baldrs draumar" (full text) edited on facing pages by Odd Einar Haugen from the manuscripts Reykjavik, Arnamagnaean Collection, GKS 2365 4to, and Copenhagen, Arnamagnaean Collection, AM 478 I a 4to, respectively. This is part of a volume on the Nordic languages in the Middle Ages.